UPAYA MENINGKATKAN AKTIVITAS BELAJAR PENDIDIKAN KEWARGANEGARAAN (PKn) MELALUI MODEL PEMBELAJARAN CONTEXTUAL TEACHINGAND LEARNING (CTL) - Dwinanto Arif Kurniawan; Trisharsiwi Trisharsiwi (Universitas Sarjanawiyata Tamansiswa, 2015)
Â Abstract: The purpose of this research is to know the improving of learning activities of PKn by using Contextual Teaching and Learning (CTL) among the sixth grade students of state elementary school 4 Karangduwur Petanahan, Kebumen. The research methodology was by using action research with collaborative style and it was done in two cycles. The subjects of this research were 23 students of State Elementary School 4 Karangduwur Petanahan, Kebumen grade VI in even semester and it consists of 11 male students and 12 female students. The object of this research was the students learning activities in Civic Education Material by using Contextual Teaching and Learning (CTL) learning Style. This research used Kemmis and MC Taggart Style. The steps were planning, realization, observation, and reflection. The technique of the data collection in this research was done by using observation sheets and documentation. The technique of data analysis was the observation sheets which were observed during the learning process from the beginning till the end of the class and it was done with percentage in each indicator. The finding of the research show that after applying this Contextual Teaching and Learning (CTL) learning Style in State Elementary School 4 Karangduwur Petanahan, Kebumen grade VI, learning activities has improved. It is indicated by the improving in the average percentage of student active learning in its cycle. It is indicated in the cycle I is 65,5% and it has improved in the cycle 2 become 81,8%. By this, it can be concluded that this classroom action research can improve the Civic Education learning activities of State Elementary School 4 Karangduwur Petanahan, Kebumen grade VI because it has completed success indicators, i.e. 75% of success indicator.Â